Hypersensitivity reactions to non‐steroidal anti‐inflammatory drugs (NSAIDs) – a retrospective study. (28th September 2020) - Angeletti, Flavia; Meier, Franziska; Zöller, Nadja; Meissner, Markus; Kaufmann, Roland; Valesky, Eva Maria
Summary: Background: The aim of this study was to verify the validity of clinical history and oral provocation challenges of patients with NSAID hypersensitivity and to identify safe alternatives. The COX‐2 inhibitor etoricoxib, in particular, was studied. Patients and methods: In all, 104 patients with confirmed diagnoses of NSAID hypersensitivity treated at the Department of Dermatology, Frankfurt University Hospital, Germany between 2004 and 2012 were retrospectively studied. Results: The medical history and hypersensitivity symptoms during oral provocation testing (OPT) largely coincided and were mostly mild to moderate. Acetylsalicylic acid (ASA) was the most frequent trigger both anamnestically (27.9 %) and during OPT (47.8 %). Etoricoxib caused the fewest reactions during OPT (4.2 %). Acetaminophen led to reactions in only 6.7 % of the cases studied although it was named more often in clinical histories (14 %). Conclusions: OPT should be the aim whenever possible as most symptoms are mild to moderate. To distinguish between selective and cross‐hypersensitivity reactions, ASA should be part of the test protocol. Furthermore, the findings of this study indicate that etoricoxib and acetaminophen are safe treatment alternatives in case of NSAID hypersensitivity. However, these drugs should not be administered without prior OPT in an inpatient setting, as severe symptoms can occur.